KOMPETENSI DAN KOMITMEN ORGANISASI KAITANYA PADA MOTIVASI DAN KINERJA PEGAWAI - Marita Diansyah; Handry Sudiartha Athar; Achmad Fauzi (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2020)
This study aims to analyze the effect of competence and organizational commitment on employee performance with motivation as an intervening variable in the Department of Education and Culture of the City of Bima. This study's population is 55 Civil Servants at the Bima City Education and Culture Office, of which all employees are the research samples. Measurement of variables is using a Likert Scale. The analysis technique used in this study is Path Analysis. The results showed that competence has a significant effect on employee performance, but motivation does not mediate competence. In contrast, organizational commitment does not significantly influence employee performance. The author suggests that the City of Education and Culture Office of Bima improve employee performance by increasing employee competency by providing employees opportunities to improve their education levels and involving employees in various education and training programs the primary function.